2014
DOI: 10.1186/1471-2164-15-452
|View full text |Cite
|
Sign up to set email alerts
|

Gene co-expression network analysis identifies porcine genes associated with variation in Salmonella shedding

Abstract: BackgroundSalmonella enterica serovar Typhimurium is a gram-negative bacterium that can colonise the gut of humans and several species of food producing farm animals to cause enteric or septicaemic salmonellosis. While many studies have looked into the host genetic response to Salmonella infection, relatively few have used correlation of shedding traits with gene expression patterns to identify genes whose variable expression among different individuals may be associated with differences in Salmonella clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 52 publications
4
41
0
Order By: Relevance
“…Other genes found in the present research and related to inflammatory conditions of the adipose tissue in FAT pigs are particularly interesting to mention: CD163, a member of the scavenger receptor cysteine-rich superfamily (Guo et al 2014;Smith et al 2014); solute carrier family 11 (protoncoupled divalent metal ion transporter), member 1 (SLC11A1), a gene involved in resistance to Salmonella infection (Kommadath et al 2014); chemokine (C-C motif) receptor 1 (CCR1), which was previously found to be overexpressed in obese pigs (Kogelman et al 2014); BCL2-related protein A1 (BCL2A1), a gene found to be overexpressed in pigs with a high obesity index and that is related to immunity, inflammatory pathways and osteoclast differentiation (Kogelman et al 2014); and CD1a molecule (CD1A; indicated as PCD1A in the cited paper), a surface antigen involved in immunity that was found to be overexpressed in obese pigs by Kogelman et al (2014). The same authors highlighted a strong connection between fat deposition on the body (obesity), immunity and bone development.…”
Section: Genes Involved In Immunity and Inflammation Are More Highly mentioning
confidence: 98%
“…Other genes found in the present research and related to inflammatory conditions of the adipose tissue in FAT pigs are particularly interesting to mention: CD163, a member of the scavenger receptor cysteine-rich superfamily (Guo et al 2014;Smith et al 2014); solute carrier family 11 (protoncoupled divalent metal ion transporter), member 1 (SLC11A1), a gene involved in resistance to Salmonella infection (Kommadath et al 2014); chemokine (C-C motif) receptor 1 (CCR1), which was previously found to be overexpressed in obese pigs (Kogelman et al 2014); BCL2-related protein A1 (BCL2A1), a gene found to be overexpressed in pigs with a high obesity index and that is related to immunity, inflammatory pathways and osteoclast differentiation (Kogelman et al 2014); and CD1a molecule (CD1A; indicated as PCD1A in the cited paper), a surface antigen involved in immunity that was found to be overexpressed in obese pigs by Kogelman et al (2014). The same authors highlighted a strong connection between fat deposition on the body (obesity), immunity and bone development.…”
Section: Genes Involved In Immunity and Inflammation Are More Highly mentioning
confidence: 98%
“…Two data sets, ERP004640 and SRP018524, were selected to analyse PAS function under a different androstenone level and salmonella inoculation, respectively2729, including biological replications as well as control and treatment conditions. PAS was first discovered from the two data sets; then, PASs with different usages and their associated genes were identified for gene functional analysis in terms of corresponding conditions (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The whole blood samples were collected at day 0 and day 2 after the inoculation of pigs with salmonella. A total of 32 RNA libraries were sequenced in 50-bp single-end reads (ERP004640)29.…”
Section: Methodsmentioning
confidence: 99%
“…Again, this variation has a genetic component, suggesting it could be possible to improve food safety by selecting for pigs that more rapidly become non-shedders. In this case, RNAseq analysis of whole blood samples from persistent and low-shedding animals identified genes whose expression level was associated with variation in shedding (Kommadath et al, 2014). Furthermore, when blood taken from the same animals prior to infection was analyzed, this difference in gene expression was also present.…”
Section: Variation In Susceptibilitymentioning
confidence: 94%